Vienna Convention on the Law of Treaties A Commentary (Springer Berlin Heidelberg, 2018)
The Commentary on the Vienna Convention on the Law of Treaties provides an in-depth article-by-article analysis of all of the Vienna Convention's provisions. Each provision's analysis consists of (I) Purpose and Function of the Article, (II) Historical Background with Negotiating History, (III) Elements of the Article and finally (IV) Treaties of International Organizations. In short, the present Commentary contains a comprehensive legal analysis of all aspects of the international law of treaties. Furthermore, where the law of treaties reaches into other fields of international law, e.g. the law of state responsibility, the relevant interfaces are discussed and contextualized. With its focus on international practice, the Commentary is an invaluable reference for both academia and practitioners of international law.